METODOLOGI PENAFSIRAN QURAISH SHIHAB TERHADAP AYAT-AYAT PENDIDIKAN - Ujang Muhaemin (Institut Agama Islam Persis Bandung, 2021)
Abstract The focus of this research problem is education, as stated by Said Agil, there is a tendency that Islamic education in Indonesia is not entirely based on the Qur'an which contains various life systems. Religious education in Indonesia is often faced with various problems related to a system such as those included in the education component (objectives, curriculum, evaluation, methods and so on). Likewise, according to Quiraish Shihab, as a figure who has a qualified background in the field of interpretation (compared to other Indonesian figures), as well as his involvement as a consortium administrator in the field of education, he is of the opinion that Muslims often distort meaning. the notion of education only as a school, even though in the view of the Qur'an education has a very broad scope of meaning and does not recognize the word stop. On this basis, Quraish Shihab argues that the purpose of education according to the Qur'an is to foster students to be able to become caliphs of Allah. In an effort to make students the caliph of Allah, the Qur'an mentions various methods, one of which is the story method. Based on the description above, as well as the urgency of the demands for an understanding of al-Qur'an-based education, it is necessary to conduct further research on Quraish Shihab's interpretation of educational verses in the interpretation of al-Misbah. In practice, this research is more emphasized on the study and study of Quraish Shihab's interpretation in his commentary, as well as the literature related to this research. In accordance with the object of this research, the data collection technique used is the study and assessment of library materials (book survey). For this purpose, primary and secondary data sources are used. The main sources in this research are books written directly by Quraish Shihab. Keywords: education, al-Qur'an, interpretation, story method Abstrak Masalah yang menjadi fokus penelitian adalah pendidikan, sebagaimana dikemukakan Said Agil, terdapat kecenderungan bahwa pendidikan Islam di Indonesia belum sepenuhnya dilandasi al-Quran yang memuat berbagai sistem kehidupan. Pendidikan keagamaan di Indonesia seringkali berhadapan dengan berbagai problematika yang terkait dengan sebuah sistem seperti yang termasuk dalam komponen pendidikan (tujuan, kurikulum, evaluasi, metode dan lain sebagainya). Demikian halnya menurut Quiraish Shihab, sebagai seorang tokoh yang mempunyai background yang mumpuni dalam bidang tafsir (jika dibanding dengan tokoh Indonesia lainnya), serta keterlibatannya sebagai pengurus konsorsium bidang pendidikan, beliau berpendapat bahwa masyarakat muslim seringkali mendistorsi makna pendidikan hanya sebatas sekolah, padahal dalam pandangan al-Quran, pendidikan mempunyai jangkauan makna sangat luas dan tidak mengenal kata henti. Atas dasar itulah, Quraish Shihab berpendapat bahwa tujuan pendidikan menurut al-Quran adalah membina anak didik sehingga ia mampu menjadi khalifah Allah. Dalam upaya menjadikan anak didik sebagai khalifah Allah, al-Quran menyebutkan berbagai macam metode, yang salah satu diantaranya adalah metode kisah. Berdasarkan uraian di atas, sereta mendesaknya tuntutan pemahaman pendidikan berdasarkan al-Quran, kiranya perlu dilakukan penelitian lebih lanjut terhadap penafsiran Quraish Shihab tentang ayat-ayat pendidikan dalam tafsir al-Misbah. Dalam operasionalnya penelitian ini lebih ditekankan pada penelaahan dan pengkajian terhadap penafsiran Quraish Shihab dalam karya tafsirnya, serta litelatur-litelatur yang ada hubungannya dengan peneletian ini. Sesuai dengan obyek penelitian ini, maka teknik pengumpulan data yang digunakan adalah penelahan dan pengkajian terhadap bahan-bahan pustaka (book survey). Untuk keperluan tersebut digunakan sumber data primer maupun skunder.Sumber primer dalam penelitian ini adalah buku-buku yang ditulis langsung oleh Quraish Shihab. Kata Kunci: pendidikan, alqur’an, tafsir, metode kisah